Gene–environment interaction in autoimmune disease. (7th March 2014) - Ellis, Justine A; Kemp, Andrew S; Ponsonby, Anne-Louise
Abstract : Autoimmune disease manifests in numerous forms, but as a disease group is relatively common in the population. It is complex in aetiology, with genetic and environmental determinants. The involvement of gene variants in autoimmune disease is well established, and evidence for significant involvement of the environment in various disease forms is growing. These factors may act independently, or they may interact, with the effect of one factor influenced by the presence of another. Identifying combinations of genetic and environmental factors that interact in autoimmune disease has the capacity to more fully explain disease risk profile, and to uncover underlying molecular mechanisms contributing to disease pathogenesis. In turn, such knowledge is likely to contribute significantly to the development of personalised medicine, and targeted preventative approaches. In this review, we consider the current evidence for gene–environment (G–E) interaction in autoimmune disease. Large-scale G–E interaction research efforts, while well-justified, face significant practical and methodological challenges. However, it is clear from the evidence that has already been generated that knowledge on how genes and environment interact at a biological level will be crucial in fully understanding the processes that manifest as autoimmunity.